IMPLEMENTASI VIRTUAL REALITY DAN GRATITUDE THERAPY UNTUK REDUKSI NYERI DAN STRES PADA IBU POST SECTIO CAESAREA DI KABUPATEN BUNGO - citra indah fitriwati (Stikes Syedza Saintika Padang, 2025)
Postoperative pain and postpartum stress are two major issues commonly experienced by mothers who undergo sectio caesarea delivery. Poorly managed pain can increase stress, delay the recovery process, and interfere with mother–infant bonding. This study aimed to identify the effect of virtual reality and gratitude therapy on pain and stress among post-cesarean section mothers, who often face more complex physical and emotional challenges. This research employed a quasi-experimental design with a one-group pretest–posttest approach and was conducted in July–August 2025 with 50 participants. Data were analyzed using an independent t-test. Pain was measured using Numeric Rating Scale, and stress was assessed using Perceived Stress Scale. Results showed that 68% of respondents were aged 20–35 years, 48% had a college education, 60% were working mothers, 80% were multigravida, and 82% had a history of previous sectio caesarea. Statistical analysis revealed a significant difference in pain and stress scores after the intervention, with a p-value of 0.0005. These findings suggest that virtual reality combined with gratitude therapy can serve as an effective non-pharmacological intervention for reducing pain and stress in post-sectio caesarea mothers.Keywords: Virtual reality; Gratitude therapy; Pain; Stress; Sectio caesarea